Perancangan Resor Wisata Pesisir Berbasis Arsitektur Tropis: Studi Pengembangan Kawasan Pantai Botubarani - Dimas Arya Prayoga; Ernawati Ernawati; Dara Fitriani (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study formulates a design concept for the Beach Tourism Resort Area in Botubarani Village by applying tropical architecture that responds to coastal climatic conditions while enhancing the quality of visitor experiences. The research integrates principles of thermal comfort, environmental sustainability, and the ecological potential of coastal environments as the basis for creating climate-adaptive and environmentally responsive tourism areas. The methodology includes site analysis, field observation, climatological assessment, and a literature review related to tropical architecture and coastal tourism design. The collected data were used to determine building orientation, mass layout patterns, visitor capacity, materials, vegetation, and utility systems appropriate for humid tropical climates. The findings show that the site’s position between the sea and the mountains, combined with full-day sun exposure, requires design strategies that maximize cross-ventilation, utilize sloped roofs, provide natural shading, and apply local materials such as wood, bamboo, and red brick. The large spatial needs based on visitor capacity projections are accommodated through a flexible cluster layout that supports visual and functional connectivity between buildings while incorporating green open spaces to enhance microclimate comfort. The utility system is designed using sustainability principles through greywater–blackwater separation, infiltration wells, and recycling-based waste management. This study confirms that the application of tropical architecture in coastal tourism areas can improve thermal comfort, energy efficiency, and environmental sustainability. These findings guide developing tropical tourism area designs that are more adaptive to climate change and more responsive to visitor needs.